SISTEM PENGENALAN OTOMATIS DIAMETER CITRA MANTOUX UNTUK DETEKSI DINI PENYAKIT TBC KELENJAR - Sri Hadianti; Dwiza Riana (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2018)
The Mantoux test is a test performed to detect tuberculosis, a test performed by injecting protein into the skin tissue of the left hand, this testis mostly done because it feels more accurate the results, the way the Mantoux test works is to measure the diameter of the protein-given area, if the diameter is less than 5 mm, the patient is not diagnosed with tuberculosis, but if the diameter of the area given by the protein exceeds 5 mm then the patient is diagnosed with tuberculosis. To help simplify the calculation, the area of the Mantoux test needs to be image processing. In this study image processing uses K-Means clustering method with edge detection, then the calculation of diameter after edge detection. And the end result is the image of the Mantoux test area can easily be calculated in diameter, without having to make measurements using a manual ruler.